(untitled) (Bangladesh Heart Journal, 2016)
Background: Bilateral internal thoracic artery (BITA) grafting is associated with improved long-term survival and graft patency compared to single internal thoracic artery (SITA) graft and saphenous vein graft in coronary artery bypass grafting (CABG). However, BITA grafting may adversely affect early in hospital mortality and morbidity due to deep sternal wound infection. Hence, we carried out this study to evaluate early outcomes of BITA grafting in different configuration in our hospital and to assess safety and applicability of BITA grafting as a routine procedure. Methods: A retrospective cross sectional study was conducted in September 2014 where all 134 patients using bilateral ITA for coronary artery bypass (CABG) at United Hospital, Dhaka, Bangladesh from January 2009 to September 2014 were included. BITA grafting were used in either in-situ or Y-graft technique. We reviewed and evaluated patients characteristics and short-term outcomes. The short-term outcomes included in hospital mortality and major morbidities. Results: Out of 134 patients, 129 (96%) patients were male. The mean age was 48.73 ± 8.42 yrs ranging from 28 to 72 yrs. Hypertension and smoking were the most common cardiac risk factors. There was no mortality in both BITA in-situ and BITA Y-graft groups. Most common postoperative complications were fever (26%), and arrhythmia (7.5%). Only one female patient (0.7) had sternal wound complication. Elderly, obesity and COPD were not observed to be associated with sternal wound complication. Conclusion: Short-term outcomes of BITA grafting for CABG is excellent with no significant difference between BITA in-situ and BITA Y-graft groups. Bangladesh Heart Journal 2016; 31(1) : 3-9